2009
DOI: 10.1021/ma9004764
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Enhanced Crystallization in Impact-Resistant Polypropylene Copolymer: Influence of Compositional Heterogeneity and Phase Structure

Abstract: The roles of compositional heterogeneity and phase structure on an unusual shear-enhanced crystallization behavior of impact-resistant polypropylene copolymer (IPC) were systematically investigated by differential scanning calorimetry (DSC), polarized optical microscopy (POM), field emission transmission electron microscopy (FETEM), and scanning electronic microscopy (SEM). Upon an interval of preshearing, we observed an amazing accelerated crystallization in IPC, whereas no such shear-enhanced crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 62 publications
0
52
0
Order By: Relevance
“…On the DSC endotherms, the melting peaks located at around 165 and 152 C belong to the a-and bmodifications, respectively, and the lower melting peak at around 115 C is attributed to the melting of crystalline segments in EPB. 5 It clearly shows that Table I. In brief, the outcomes of DSC and WAXD confirm that the dominantly crystalline modifications are a-and b-forms in a-and b-IPCs, respectively.…”
Section: Crystalline Modificationmentioning
confidence: 60%
See 1 more Smart Citation
“…On the DSC endotherms, the melting peaks located at around 165 and 152 C belong to the a-and bmodifications, respectively, and the lower melting peak at around 115 C is attributed to the melting of crystalline segments in EPB. 5 It clearly shows that Table I. In brief, the outcomes of DSC and WAXD confirm that the dominantly crystalline modifications are a-and b-forms in a-and b-IPCs, respectively.…”
Section: Crystalline Modificationmentioning
confidence: 60%
“…Early studies on IPC showed that it has complex composition and phase structure. [5][6][7] That is, in addition to the main components of crystalline iPP and amorphous ethylenepropylene random copolymer (EPR), there also exist some partially crystalline ethylene-propylene block copolymers (EPBs) with varying segmental lengths, and all of these components combine into a complex core-shell multilayer structure. So far, the most concerned topic in the research of IPC is clarifying the origination of its excellent rigidity-toughness balance property.…”
Section: Introductionmentioning
confidence: 99%
“…First, either for the unannealed sample (IPC-23) or for the annealed samples, they exhibit two different particle morphologies. The black holes represent the rubber particles (as shown by dash circle, A), in which EPR and PE (possibly containing a few amount of iPP) form the ideal core-shell structure, namely, PE (possibly containing a few amount of iPP) is completely wrapped by EPR [11,12] . During the etching process using n-heptane, the inner core is also taken away when EPR is dissolved.…”
Section: Morphological Changes Of Rubber Particlesmentioning
confidence: 99%
“…The formation of such multiphase structure is mainly related to the special polymerization process, namely, the bulk polymerization of propylene is first carried out and then the copolymerization of propylene and ethylene is subsequently promoted [810] . Several researches prove that IPC exhibits a multilayered core-shell structure of rubber particles: PE and a part of iPP act as an inner core while EbP acts as an outer shell, and between the inner core and the outer shell, there is an intermediate layer that is mainly related to EPR [11,12] . Consequently, EbP shows the compatibilizing effect to intensify the interfacial interaction between iPP matrix and rubber particles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that the great viscosity difference and good compatibility between EPR and EbP component result in the special dispersed phase consisted of EPR and EbP in IPC [5,8] . For the dispersed phase, the core-shell structure is composed of an EbP core (with long ethylene chain segment) and two shells, the outer EbP layer (with long propylene chain segment) and the inner EPR one [5,31,32] . Here, the EPR shell could be observed clearly by etching while the outer EbP shell, located at the interface, is difficult to define by SEM.…”
Section: Phase Morphologymentioning
confidence: 99%